THE DISAVOWAL OF THE BODY AS A SOURCE OF INQUIRY IN CRITICAL DISABILITY STUDIES: THE RETURN OF IMPAIRMENT? - Miceli, Michael (Critical Disability Discourses, 2010)
This paper is a critical exploration of how the human body has been excluded or disavowed as a source of inquiry within the nascent field of Critical Disability Studies and from the social model of disability. The locus of scholarly interest has remained singularly on disability to the neglect of examining impairment. This reluctance to address issues of impairment highlights a tension within the disability rights movement on a gender axis. Men with disabilities are more concerned with focusing on “disabling” external barriers, such as unequal access and negative attitudes, at the expense of personal (and bodily) experiences of impairment, which is a concern for women with disabilities. This paper is also an attempt at giving voice to what Crow (1996) has referred to as a “return to impairment” as a means of renewing the social model of disability. Keywords: impairment, embodiment, pain, chronic illness, corporeal disability discourse, social model of disability, “healthy disabled”